Eksistensi Kesenian Sikambang Sebagai Pewarisan Budaya Pada Acara Pernikahan Masyarakat Pesisir di Kelurahan Lopian Kecamatan Badiri Kabupaten Tapanuli Tengah - Rizqa Mulya Sari Lubis; Puspitawati Puspitawati; Payerli Pasaribu (Program Studi Antropologi Sosial Pascasarjana Universitas Negeri Medan, 2022)
This study attempts to understand its art sikambang performances, know and described values contained in a art sikambang , and he knows existence art sikambang as the inheritance culture in wedding events the coastal communities in urban village lopian, kecamatan badiri. Research methodology used is the method research qualitative conducting observations non of participation (non participant an observer and documentation, and interview. The result shows that art of sikambang is art the coastal communities which includes what, rhyme, song, martial arts or dampeng followed by music coastal, and stage basikambang carried out in wedding events. Values are contained in the arts of sikambang like a religion, value education, moral value, of the cultural and the value of aesthetics used as the guidance of the lives of the community coastal. The inheritance of the cultural at a show art sikambang through a process internalization, the socialization process, and the process of enkulturasi.